Potential influence of Yucca extract as feed additive on greenhouse gases emission for a cleaner livestock and aquaculture farming - A review. (1st December 2019) - Adegbeye, Moyosore Joseph; Elghandour, Mona M.M.Y.; Monroy, Jose Cedillo; Abegunde, Taye Olurotimi; Salem, Abdelfattah Z.M.; Barbabosa-Pliego, Alberto; Faniyi, Tolulope O.
Abstract: Creating a balance between minimizing environmental impacts and intensification, of livestock and aquaculture, is important to ensure sustainable animal-protein production. Application of natural additives that are suitable for cleaner animal production is a necessity. Yucca schidigera is capable of this and because it could grow in desert area, makes it a potential asset in the face of global warming-related climate changes. Thirty-five studies were used as data, which include in vitro and in vivo evaluations. About 43%, 28.6% and 31% were proportion of ruminant, monogastric and aquaculture species used for this study. Yucca schidigera showed that it is capable of reducing aerial ammonia concentration in pens, and ammonia odour from manure. In ruminant, Yucca could reduce methane emission, lower nitrous oxide emission, reduce urinary and fecal nitrogen. Yucca extract could be used to improve water quality by reducing the concentration of total ammonia nitrogen and nitrate in fresh and marine water used for aquaculture. Therefore, to reduce livestock footprint, Yucca may be included in the diet of cattle, sheep, goat, horses, rabbit, fishes, and shrimps with a positive result. The reviewed publications provide strong support for the use of Yucca extract as feed additive to reduce nutrient excretion and environmental impact of animal-protein production. This study, however, shows that there is need for more in vivo studies of Yucca in swine rabbit, horses and even poultry. Graphical abstract: Image 10544 Highlights to Reviewers: Yucca schidigera extract could be used to reduce methane emission from ruminant. Extract of Yucca reduced urinary Nitrogen and Nitrous oxide emission from feces. Yucca in the diet of fishes reduced total NH3 –N concentration in water. Yucca improved water quality and reduced NH3 in lakes water and culture effluent. Yucca reduced NH3 odorous emission from poultry manure, pig and equine pen.